Thoreau and Spadina Dreamers Unite: Idealistic Communities in Canadian Publishing - Ravvin, Norman (Text Matters: A Journal of Literature, Theory and Culture, 2015)
The rise of Canadian national identity in the 1960s contributed to a flourishing small press movement across the country. One of the most impressive, long-standing and influential presses of this era was Coach House Press, located near the University of Toronto. Book design, creative forms of editing, collaborative and community-oriented work all became a focus of idealism in the Coach House context, as its founders borrowed from earlier international models, but relied, too, on the Canadian moment to devise new ways to disseminate and create literary culture. More recently, a similar idealistic model in publishing and press work has appeared in Nova Scotia at Kentville’s Gaspereau Press. Gaspereau’s founders, like those at Coach House, have searched for an alternative plan and method- through an in-house dedication to the craft of design and bookmaking- that is unlike that applied by mainstream publishers. One could argue that the two outfits represent a counter-tradition in Canadian cultural life, a dedication to artisanal work, as well as to forms of collaborative editing and design. With the publishing and bookselling industry under great pressure in Canada from shifts in technology and government support, counter-traditional models like Gaspereau Press present the possibility of unique forms of cultural output and marketing. Behind such efforts we recognize philosophies and notions of cultural community that run counter to major trends. This paper examines the history of both presses, specific publications, and the impact of such work on the broader Canadian literary scene.